Bankruptcy Prediction Analysis with the Altman Z–Score, Springate and Zmijewski Models in Fisheries Sub Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 Period - Theresia Sitorus, Yohana Carla (Dinasti Publisher, 2023)
This article aims to determine the potential for bankruptcy in fisheries sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2021. The scope of discussion in this article is financial management. The analytical tool used in this article is the Altman Z-Score, Springate and Zmijewski bankruptcy prediction models. There are three fishing companies that are the object of research in this article, namely PT Era Mandiri Cemerlang, TBK, PT Morenzo Abadi Perkasa, TBK and PT Asia Sejahtera Mina, TBK. From research on the three companies, test results obtained with the Altman Z-Score model, PT Era Mandiri Cemerlang have the potential to experience bankruptcy, PT Morenzo Abadi Perkasa has a gray area condition and PT Asia Sejahtera Mina is in a healthy condition. Test results with the PT Era Mandiri Cemerlang Springate model, TBK is in a state of bankruptcy, while PT Morenzo Abadi Perkasa and PT Asia Sejahtera Mina are in good health. The test results with the Zmijewski model of the three fishing companies are in a sound financial condition and have no potential for bankruptcy. Of the three bankruptcy prediction models, the one with the highest accuracy is the Zmijewski model.